2023
DOI: 10.3390/foods12030585
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Biomarkers in Traditional Starter Determine the Chemical Characteristics of Turbid Rice Wine from the Rim of the Sichuan Basin, China

Abstract: The fungal community in Qu plays a key role in the formation of turbid rice wine (TRW) style. The Sichuan Basin and its surrounding areas have become one of the main TRW production regions in China; however, the fungal community in Qu and how they affect the characteristics of TRW remain unknown. Therefore, this study provided insight into the fungal biomarkers in Qu from Guang’an (GQ), Dazhou (DQ), Aba (AQ), and Liangshan (LQ), as well as their relationships with compounds in TRW. The main biomarkers in GQ we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The colony count was expressed as colony-forming units per milliliter (CFU/mL). Soluble solids were determined using a handheld refractometer [13], pH was measured using a pH meter [14], and reducing sugar content was determined using the DNS (3,5-dinitrosalicylic) method [15].…”
Section: Determination Of Colony Count and Basic Physicochemical Indi...mentioning
confidence: 99%
“…The colony count was expressed as colony-forming units per milliliter (CFU/mL). Soluble solids were determined using a handheld refractometer [13], pH was measured using a pH meter [14], and reducing sugar content was determined using the DNS (3,5-dinitrosalicylic) method [15].…”
Section: Determination Of Colony Count and Basic Physicochemical Indi...mentioning
confidence: 99%
“…At present, Pu and Yan (2022) found differences in fungal community structures and physicochemical properties in pit mud samples from different spatial positions within Nongxiang Baijiu fermentation cellars, revealing unique characteristic multidimensional pit mud fungal community profiles [2]. Chen et al ( 2023) also reported on the correlation between fungal biomarkers in Jiuqu and the style of corresponding rice wine from the rim of the Sichuan Basin in Southwest China [3].…”
mentioning
confidence: 98%